Baker, Herbert (Sir) House for C.J. Rhodes Rondebosch, Cape Town. 1897 - Baker, Herbert (Sir) (My University, 2011)
Baker, Herbert (Sir). House for C.J. Rhodes. Rondebosch, Cape Town. Details. Plans. Elevations.
Details: Watercolours on Paper. 695x915. Plans: Ink on Parchment. 555x815.. Elevations: Ink on parchment. 660X710.
Keywords: Baker, Herbert (Sir). Rhodes, C.J. Rondebosch, Cape Town. Details. Plans. Elevations. Groote Schuur.